Influences of the Corded Ware Culture in the Belarusian Lakeland (on the Ground of the Kryvina Peat-Bog Microregion) - Charniauski Маxim (Archaeologia Lituana, 2017)
This article analyzes the cultural development of the Neolithic settlements in the Belarusian Lakeland at the 4th–3rd millennium BC, mainly based on the archaeological studies on the Kryvina peat-bog settlements. Although cultural complexes of analyzed settlements of the successive Usviaty and Northern Belarusian cultures are quite similar, the latter one possesses a noticeable and significant influence of the Corded Ware tradition that had reached the region from the north-west and south. Based on the obtained radiocarbon dates, this cultural change took place in the second half of the second quarter of the 3rd millennium BC. This is also related with the beginning of the manifestations of the Corded Ware tradition’s influence in the region.